Developing Relationships with Alumni - Payne, Rodger M. (Bulletin for the study of religion, 2020)
For a small departmentin the humanities, it can be difficult to maintain the numbers needed for graduating students each semester. Dr. Rodger M. Payne, Chair of the Religious Studies Department at the University of North Carolina—Asheville found a way to promote student involvement within his department that has proven beneficial well past the student’s’graduation. Despite beginning this work in 2009 following an economic recession, Payne set about increasing student engagement via social events which his department hosted, inviting both majors and minors to join these events. In so doing, he created an atmosphere where the students—who often had commitments to other majors—felt valued and formed a connection to the department that they would maintain even as alumni of UNC.